ENZYME ENHANCED OIL RECOVERY (EEOR) USING LAKASE FROM Marasmiellus palmivorus (Sharples) Desjardin (comb. prov.) - Arya Rumintang, Sandi
Energy needed for the wide range of human activities still mainly comes from non-renewable petroleum fuels. Therefore, it becomes important to maximize and to enhance the oil recovery process. Extracellular enzymes from fungi can be one solution to the problems from oil recovery to enhance oil recovery (EOR). Laccase is one of several enzymes from fungi which can oxidize hydrocarbons. Unfortunately, to date there is no method for selecting suitable enzymes for enzyme enhance oil recovery (EEOR) applications. This study was aimed to determine the potential use of laccase in EEOR. In this study, laccase was produced from Marasmiellus palmivorus by using cultivation in a static solid state fermentation (SSF) reactor with lignocellulosic as substrate. To study the potential use of laccase in EEOR, oil viscosity was measured, then GC-MS was used to determine the oil content before and after oxidation by laccase and followed with core flood experiments. Core flood experiments were performed with heavy crude oil and cores consistly of quartz sand with a porosity of 20%. The results showed that the laccase crude extract used in this study had a specific activity of 626 U/g. Viscosity test results by using a rheometer showed that at room temperature, laccase can reduce the viscosity of oil by 10.6% from 61.9 cP to 55.3 cP. There are two aromatic hydrocarbon compounds disappear after petroleum oxidized by laccase, 2-hexyl-3-phenyl-2-propenal and naphthalene, 1,2,3,4-tetramethyl, respectively. Results of core flood experiments showed that laccase can increase oil production by up to 33% after waterflooding at a temperature of 70 °C. Based on these laboratory-scale research it could be concluded that laccase has a potential to be used in EEOR.